Functionalized Single‐Walled Carbon Nanohorns to Reinforce Sulfonated Poly(ether ether ketone) Electrolyte for Direct Methanol Fuel Cells. Issue 17 (1st September 2020) - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, Sreekuttan M.
Abstract: Carbon‐nanomaterial‐based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single‐wall carbon nanohorns (f‐SWNHs) are realized as an additive in sPEEK. The −COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f‐SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f‐SWNHs shows improved electrochemical selectivity of 17.03×10 −4  Scm −3 s and delivers the highest peak power density of 230 mW cm −2 in DMFCs. Abstract : sPEEK now : Functionalized single‐wall carbon nanohorn additives in sulfonated poly(ether ether ketone) (sPEEK) show enhanced proton conduction and reduced methanol permeability